2000
DOI: 10.1038/sj.leu.2401783
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of 2-chloro-2′-deoxyadenosine with cyclophosphamide in patients with pretreated B cell chronic lymphocytic leukemia and indolent non-Hodgkin's lymphoma

Abstract: Because of their substantial in vitro synergy, we conducted a dose-escalation study of cyclophosphamide (CP) added to 2-chloro-2′-deoxyadenosine (CdA) in patients with previously treated chronic lymphocytic leukemia and non-Hodgkin's lymphoma. CdA was given at a fixed dose (5.6 mg/m 2 /day) as a 2-h intravenous (i.v.) infusion, immediately followed by a 1-h i.v. infusion of CP, for 3 days. The initial daily CP dose was 200 mg/m 2 , and was escalated by 100 mg/m 2 increments in successive cohorts of three to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…[42][43][44]50 Favorable interactions have been shown between various nucleoside analogs and DNA-damaging agents, leading to clinical trials. 6,19,51,52 In conclusion, we demonstrate for the first time that CdA inhibits the resynthesis step of DNA repair in B-CLL cells, and that this may be the basis (entirely or partially) for the synergism between CdA and UV light or alkylating agents. This advocates the combination of CdA with agents provoking DNA damage, a strategy that could help to circumvent resistance due to enhanced DNA repair.…”
mentioning
confidence: 58%
“…[42][43][44]50 Favorable interactions have been shown between various nucleoside analogs and DNA-damaging agents, leading to clinical trials. 6,19,51,52 In conclusion, we demonstrate for the first time that CdA inhibits the resynthesis step of DNA repair in B-CLL cells, and that this may be the basis (entirely or partially) for the synergism between CdA and UV light or alkylating agents. This advocates the combination of CdA with agents provoking DNA damage, a strategy that could help to circumvent resistance due to enhanced DNA repair.…”
mentioning
confidence: 58%
“…[50][51][52][53][54] Because alkylating agents and nucleoside analogues have been shown to be effective, combinations of these agents have been tested, and response rates of 58% to 88% have been observed. [55][56][57] The addition of rituximab to these agents has been well tolerated with little additional toxicity and appears to further increase the response rate. 58-60 Recent studies using the proteasome inhibitor bortezomib in combination with rituximab have found this combination to be effective.…”
Section: Choice Of Initial Therapymentioning
confidence: 99%
“…In the trials finished to date, alkylating drugs and anthracyclines with mitoxantrone were most often combined with either FAMP or with 2-CdA. [10][11][12][13][14][15][16][17][18]29,30 Our study is the first, to our knowledge, in which previously Table 4 CMC-induced grade III and IV non-hematological side-effects n, number of patients; n1, number of courses; FUO, fever of unknown origin; DIC, disseminated intravascular coagulation; IHD, ischemic heart disease. untreated CLL patients received two other drugs in combination with 2-CdA: cyclophosphamide and mitoxantrone (CMC programme).…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical studies and early clinical reports may support such a hypothesis. [10][11][12][13][14][15][16] Among cytotoxic agents, alkylating drugs and anthracyclines were the primary candidates for use in combination with purine analogs. Synergistic action of 2-CdA with cyclophosphamide and its derivatives has been shown both in in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation